EGFR trafficking: effect of dimerization, dynamics, and mutation - Schultz, Destiny F.; Billadeau, Daniel D.; Jois, Seetharama D. (Frontiers in Oncology, 2023)
Spontaneous dimerization of EGF receptors (EGFR) and dysregulation of EGFR signaling has been associated with the development of different cancers. Under normal physiological conditions and to maintain homeostatic cell growth, once EGFR signaling occurs, it needs to be attenuated. Activated EGFRs are rapidly internalized, sorted through early endosomes, and ultimately degraded in lysosomes by a process generally known as receptor down-regulation. Through alterations to EGFR trafficking, tumors develop resistance to current treatment strategies, thus highlighting the necessity for combination treatment strategies that target EGFR trafficking. This review covers EGFR structure, trafficking, and altered surface expression of EGFR receptors in cancer, with a focus on how therapy targeting EGFR trafficking may aid tyrosine kinase inhibitor treatment of cancer.